ANALYSIS OF THE MAIN CAUSES OF THE ENERGY CRISIS IN THE KYRGYZ REPUBLIC (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The article discusses the main factors contributing to the emergence of this problem. The object of the study is to identify the causes of the energy crisis in the Kyrgyz Republic, and the subject is to study the infrastructure for eliminating the energy crisis in the Kyrgyz Republic. The electric power industry is a particularly important industry for the Kyrgyz Republic. Among the States located in Central Asia, the Kyrgyz Republic has faced serious energy problems over the past decade. The main part of the electricity produced goes to the development of the economy in industry, agricultural production, etc. The Kyrgyz Republic is rich in water resources. The energy potential of the Kyrgyz Republic’s water resources is estimated at 162 billion kWh of electricity (38% of reserves in Central Asia). Therefore, carrying out a predictive analysis of the accumulation of water resources is currently an urgent issue for the Kyrgyz Republic. Currently, the level of development of all potential reserves of hydro resources of the Kyrgyz Republic is on average about 10%, of which the Naryn River basin has the highest level of development - the Toktogul HPP Cascade of almost 50% in production and capacity, located in the lower reaches of the Naryn River. And in this article it is analyzed that one of the main causes of the energy crisis are the factors of the crisis state of the power system, operation.
Keywords: Energy crisis; infrastructure; energy system; functioning; efficient use of energy; energy resource